Cyclohexanaminium trichloroacetate - Shahwar, Durre (International Union of Crystallography, 2009)
In the crystal of the title compound, C(6)H(14)N(+)·C(2)Cl(3)O(2) (−), centrosymmetric assemblies of two cyclohexanaminium cations and two trichloroacetate ions are linked by N—H⋯O hydrogen bonds, thereby forming R (4) (4)(12) ring motifs. Further N—H⋯O interactions link the tetramers into chains propagating along the a axis.